Information and Communication Technology (ICT) for Children with Special needs CWSN - Kaur, Harjinder (SAINTIS Publishing, 2022)
All students, regardless of gender, race, colour, ethnic or social origin, genetic traits, language, religion or belief, political or other opinions, participation in a national minority, property, birth, or disability, everyone has the right to an equitable education (Klironomos et al., 2006), and to be considered as being an integral part of the learning community. To view Universal Access to Education as a concrete and attainable goal, teachers must be aware of the ICT potential and be able to acquire the necessary knowledge and operational skills to select and use ICT as an appropriate and promising tool for promoting equity in educational opportunities by assisting children with special needs in overcoming barriers to learning, thereby increasing their school achievement, as well as their autonomy and willingness to learn. The paper highlighted the definition of ICT, types of ICT items and how ICT is being used and describe the benefits of ICT to students with special needs.